Histopathological and clinical correlation of cutaneous adverse drug reaction - Singh, Pooja; Jaiswal, Amit; Arora, Kapil (International Journal of Research in Dermatology, 2022)
Background: The aim was to study the histopathological features of cutaneous adverse drug reactions (ADRs) and its correlation to clinical presentation. Methods: We carried our study on 80 patients of drug reactions presented in OPD over a period of 24 months. We noted offending drug, time gap between drug intake and appearance of lesion clinically and performed biopsy to study histopathological patterns and their utility as an aid to diagnosis. WHO-UMC causality assessment method was used in few cases with due diligence. AGEP (acute generalized exanthematous pustulosis) validation score of the EuroSCAR study group was used and SCORTEN for prognosis of SJS/TEN (Stevens-Johnson syndrome/toxic epidermal necrolysis). Histopathological correlation and clinical correlation were statistically analysed. Results: The most common histopathological finding was vacuolar interface dermatitis and presence of eosinophils. The most common drug responsible was antimicrobials. Histopathological findings were most consistent in cases of FDE and AGEP and differentiating viral exanthems from maculopapular rash was challenging. Erythroderma showed varying patterns of histopathology Conclusions: Identification of histopathological patterns and clinical correlation is important for distinguishing between cutaneous ADR and the other inflammatory dermatoses. Drug reactions pose clinical challenge thus clinicopathological correlation can help in reaching diagnosis.